Study Of Satisfaction of Patients Admitted in A Tertiary Care Hospital in Nagpur - Kulkarni, M V; Dasgupta, S; Deoke, A R; Nayse (National Journal of Community Medicine, 2011)
The study was conducted with an objective to study satisfaction of patients admitted in a tertiary care hospital regarding behavior of hospital staff, cleanliness, and hospital services. Hospital based cross sectional study was carried out among indoor patients from Lata Mangeshkar Hospital which is a tertiary care hospital attached to NKPSIMS, Nagpur. Indoor `patients (n=907) discharged during the study period of four months from February 2008 to May 2008 were interviewed on the day of discharge and pre-designed proforma was filled. Data was analyzed by using Epi- info statistical software. Level of satisfaction among patients was found to be better with behavior of doctors (87.76%) as compared to behavior of nurses and Class III & Class IV workers (70.01%, 59.09% respectively) and statistically it was found to be highly significant (P<0.0001). Dissatisfaction was found to be more with cleanliness in toilets (56.01%) as compared to the other hospital areas which was also statistically highly significant (P<0.0001). Approximately only half of the patients were satisfied with quality of food available in the hospital and 16.98% patients reported availability of insufficient quantity of drinking water. Most of the patients (75%) were satisfied with overall services available in the hospital.